ROTASI KERJA, STRESS, KEPUASAN KERJA DAN KOMITMEN ORGANISASI DI PERBANKAN KOTA MALANG - Liana, Yuyuk (Fakultas Ekonomi, UIN Maliki Malang, 2013)
The main objective of this study is to find out the direct effect between job rotation, work stress towards job satisfaction, and to find out the indirect effect between job rotation, work stress towards organizational commitment through job satisfaction. The population was 52 respondent of banking employees. The results of this study provided evidence that there was a significant effect between job rotation towards job satisfaction, work stress towards job satisfaction, and job rotation towards organizational commitment; whereas between work stress towards organizational commitment, and job satisfaction towards organizational commitment showed the insignificant effect.